The colour analysis method applied to homogeneous rocks - Halász, Amadé; Halmai, Ákos (Wydawnictwo Naukowe UAM, 2015)
Computer-aided colour analysis can facilitate cyclostratigraphic studies. Here we report on a case study involving the development of a digital colour analysis method for examination of the Boda Claystone Formation which is the most suitable in Hungary for the disposal of high-level radioactive waste. Rock type colours are reddish brown or brownish red, or any shade between brown and red. The method presented here could be used to differentiate similar colours and to identify gradual transitions between these; the latter are of great importance in a cyclostratigraphic analysis of the succession. Geophysical well-logging has demonstrated the existence of characteristic cyclic units, as detected by colour and natural gamma. Based on our research, colour, natural gamma and lithology correlate well. For core Ib-4, these features reveal the presence of orderly cycles with thicknesses of roughly 0.64 to 13 metres. Once the core has been scanned, this is a time- and cost-effective method.
Keywords: radioactive waste; claystone; ImageJ; PAST; cyclostratigraphy; Hungary